Redesign of Indonesian Language Textbooks Based on Student Needs Analysis - Antonius Nesi; Yosefina Rosdiana Su; Rahayu Pristiwati (AL-ISHLAH: Jurnal Pendidikan, 2022)
The available Indonesian language textbooks, both compulsory and commercial, might not fully meet the students' future needs and industrial demands. This study examines the concept of redesigning Indonesian language textbooks based on students' needs analysis, presenting a critical review of several relevant studies from journals, conference articles, and other permanent references. This study reveals three primary results. First, teachers are responsible for evaluating the textbooks' content and determining how they can contextually adapt and modify it without losing the essence of curriculum demands. Secondly, teachers are supposed to be aware of the students' needs to facilitate the demands of the current context. A need analysis will help the teachers to get an overview of the aspects that must be adapted in Indonesian language textbooks. Thirdly, through a critical and in-depth review of the textbooks, it was found that it is necessary to redesign a model of Indonesian language textbooks, particularly the grammar textbook model, the listening and speaking skills textbook model, and the reading and writing skills textbook model. The expected product should be organized as an integrative textbook package and designed in a digital model that can be easily accessed through the network.